Contextual acceptance of insect-based foods. (October 2020) - Motoki, Kosuke; Ishikawa, Shin-ichi; Spence, Charles; Velasco, Carlos
Highlights: We studied the role of context in the acceptance of insect-based foods. Eating with friends enhanced the acceptance of insect-based foods. Eating in pubs and at food festivals enhanced the acceptance of insect-based foods. Positive arousing emotions might increase the acceptance of insect-based foods. Abstract: Insect-based foods have gained much attention as an alternative source of protein in recent years because of their high nutritional content and low production costs. However, consumer acceptance of insect-based foods still poses a big challenge in many societies. Across three studies, we examined how social companions (alone, friend, family, acquaintance, partner) and location (cafe, bar, pub, food festival) are associated with people's willingness to eat insect-based foods. We also examined the positive arousing (fun, excitement) and positive calming (romance, tranquility) emotions that were evoked by several eating contexts. The results of Studies 1 and 2 revealed that participants expected that they would be more willing to eat insect-based foods with friends (vs. alone, family, acquaintance, partner) and in pubs and at food festivals (vs. in a cafe, bar). The results of Study 3 replicated the main findings of the first two studies using the actual names (not pictures) of insect-based food products, namely 'mealworm burger' and 'cricket chocolate bar'. Moreover, these contexts, where people would be more willing to eat insect-based foods, were associated with positive arousing emotions (fun, excitement) rather than positive calming emotions (romance, tranquility). Taken together, then, these findings reveal the role of contexts associated with positive arousing emotions in eating insect-based foods and provide practical advice concerning the situations in which the consumer's acceptance of insect-based foods may be increased.